Well-targeted regulation : revisiting the role of CEO non-duality on corporate performance - GUIMARÃES, Rinaldo de Sousa (2021)
We investigate the effect of CEO non-duality on performance of publicly traded companies. We exploit a unique quasi-experiment promoted by a regulatory change in the Brazilian Stock Exchange that abolished the accumulation of Chief Executive Officer (CEO) and Chair of Board (COB) titles in companies in which pluralism was previously possible. Using a differences-in-differences research design, we find a long-lasting positive effect on firms value and weaker evidence on profitability. Our evidences dissent from prior studies that show non-duality firms underperforming their counterparts. Neither immediate market reaction nor changes in investing and financing choices explain our results. All profiles of CEO permanency are found to be beneficial, however, demotion separations experience stronger impacts. Our findings suggest that well-targeted regulations aiming at separating CEO and COB roles may enhance firm performance through improvements in decision-making processes regardless of the form of separation, thus offsetting agency costs related to the new structure.